The ‘Hikikomori’ syndrome: worldwide prevalence and co-occurring major psychiatric disorders: a systematic review and meta-analysis protocol - Andrea Pozza; Fabio Ferretti; Anna Coluccia; Takahiro Kato; Marco Gaetani (BMJ Open)
Introduction The ‘Hikikomori’ syndrome (HS) consists of prolonged and severe social withdrawal. It has been studied first in Japan and recently has increasingly drawn the attention of researchers and clinicians all over the world. It is unclear whether it exists in other cultural contexts than Asia. The existing systematic reviews did not provide a quantitative synthesis on its prevalence. In addition, a summary of the co-occurring rates of psychiatric disorders is lacking. To provide a more comprehensive understanding of the clinical picture, it seems important to investigate which psychiatric disorders listed in the classification systems are most frequently associated with this psychological condition affecting young people. This paper describes a systematic review and meta-analysis protocol summarising worldwide prevalence of the HS in general population and clinical samples with psychiatric disorders. The review will also assess the co-occurrence between HS and each psychiatric disorder defined by any version of the Diagnostic and Statistical Manual of Mental Disorders (DSM) or International Classification of Diseases (ICD) in any clinical samples with psychiatric disorders.Methods and analysis A systematic review will be conducted according to Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. Studies will be included if they use youth aged 12–35 years, recruited from general population or population with psychiatric disorders, if they use international criteria to diagnose HS. No restriction about design or language will be applied. The search will be conducted during the first week of November 2019 by two independent reviewers through the databases Scopus, PubMed, PsycINFO, Web of Science, by examining study references, by looking for conference proceedings/dissertations/theses, by contacting study corresponding authors. Random-effect meta-analysis will be performed by computing effect sizes as logit event rates. Study quality will be assessed through the Newcastle-Ottawa Scale.Ethics and dissemination The current review does not require ethics approval. The results will be disseminated through conference presentations and publications in peer-reviewed journals.PROSPERO registration number CRD 42018098747.